Evaluation of the Nguni cattle reproductive performance in the communal property association and privately owned enterprises across ecological zones of Mpumalanga Province - Sambo, Johan Mackson (My University, 2020)
The Nguni is indigenous multi-purpose cattle breed that plays an important role in both commercial and communal farming systems in South Africa (SA). Unfortunately, the breed is currently under threat of diminishing due to farmers’ preference for exotic breeds and cross breeding. In recognition of the above, the Industrial Development Corporation, the Mpumalanga Department of Agriculture, Rural Development, Land and Environmental Affairs and the University of Limpopo established the Nguni cattle breed preservation project. In this project, a herd of 30 Nguni heifers and 1 bull were allocated to 34 Communal Property Associations (CPA) and 40 private farming enterprises each. With its three distinct ecological zones (High, Mid and Low-veld), the Mpumalanga province poses a challenge to the Nguni preservation project since cattle have to adapt to different ecological zones in order to grow and reproduce efficiently. Knowledge of cattle herd productivity improves the understanding of the functional attributes and is useful in determining the constraints and the potential of communal beef cattle production systems. Significant differences between ecological zones were observed for age at first calving, weaning rate, calves’ birth weight and calves’ weaning weight (p < 0.05). Calving of heifers in the Mid-veld zone occurred earlier (24 months) on both ownership types compared to Highveld (28.09 months for private and 26.00 for CPA) and the Lowveld (28.35 months for both ownerships). Nguni cattle on the Highveld performed better in terms of weaning rate under both private and CPA ownerships, where the weaning rate were 93% and 80%, respectively. Calves birth weight was lower in both ownership types in the Midveld zone (22.17 kg), whereas in the CPA, the Lowveld zone had higher calves birth weights (26.80 kg). In the private ownership, the highest calves’ birth weight (25.35 kg) was on the Highveld. The calves weaning weight were significantly higher (p < 0.05) on Highveld in private ownership (190.16 kg) and lowest (160.39 kg) in the Midveld zone. For the CPA, the highest calves weaning weight was also on the Highveld (187.55) and lowest on Midveld (167.50 kg). A full range of backup services that are offered to the communities by stakeholders in the form of a beef package that includes veld and pasture management, nutrition management, beef performance, animal recording keeping, genetic evaluation and animal health management program needs thorough attention.
Thesis (M.A. Agricultural Management (Animal Production)) -- University of Limpopo, 2020
Keywords: Communal Property Association (CPA); Privately owned enterprises; ecological zones; age at first calving of heifers; conception rate; calving rate; weaning rate; calves birth weight and calves weaning weight; Beef cattle -- Breeding; Sexual behavior in animals; Cattle -- Reproduction